An empirical analysis of causality between development of non-bank financial intermediaries and the economic growth in malaysia - Islam, Mohd Aminul (EuroJournals Publishing, Inc, 2012)
This paper utilizes cointegration and error correction mechanism to test the causal relationship between the development of non-bank financial intermediaries (NBFIs) and per capita economic growth in Malaysia over the period 1974-2004. The study employs ARDL bounds testing approach to cointegration to determine the existence of a cointegrating relationship between non-bank financial intermediaries and economic growth. The Granger causality test in a multivariate vector error correction mechanism (VECM) framework is carried out to ascertain the direction of causality. The result suggests that nonbank financial intermediaries and economic growth are cointegrated when economic growth is used as the dependent variable but are not cointegrated when the other variables are treated as the dependent variables. The result also shows evidence of a unique long-run causality running from nonbank financial intermediaries to per capita economic growth, but not the vice versa